First record of predation of the lizard rainbow ameiva (Holcosus gaigeae) by a jaguarundi (Puma yagouaroundi) - Pérez Flores, Jonathan; Bahena Basave, Humberto; Anaya Constantino, Anthony; Weissenberger, Holger; Carballar Osorio, Javier (Therya Notes, 2025)
To date, there have been few studies on the dietary composition of the jaguarundi (Puma yagouaroundi). Previous studies mention that reptiles constitute a relatively minor component of the jaguarundi's diet, and in the majority of cases they are only identified to the family level due to the high degree of degradation of the remains observed in faeces or stomach contents. However, in this paper we report the discovery of the remains of 2 specimens of the rainbow ameiva (Holcosus gaigeae) in the stomach contents of a jaguarundi that was roadkill in the south of the state of Quintana Roo, Mexico. Identification was made possible due to the good state of preservation of the remains and the size and scale pattern of the forelimbs, which could be compared with specimens from the Herpetological Collection of the Zoology Museum of El Colegio de la Frontera Sur, Unidad Chetumal. These findings are significant in that they facilitate a deeper understanding of the trophic relationships that exist between the diverse species of the Selva Maya.